Properties of cement mortars with the addition of waste copper slag mineralized using CO₂ – preliminary study - Malazdrewicz, Seweryn; Moj, Mateusz; Nieświec, Martyna; Chowaniec-Michalak, Agnieszka; Hoła, Jerzy (Bulletin of the Polish Academy of Sciences Technical Sciences, 2026)
In response to the growing amount of copper slag, generated as a by-product of copper smelting and stored in landfills, an attempt was made to use this waste as a valuable partial replacement for natural aggregate in cement mortars. Comparative tests were conducted on four series of mortars designated as: REF – reference, GR – with the addition of copper slag, GR22, and GR50 – with the addition of slag mineralized using CO2 at temperatures of 22°C and 50°C, respectively. The article presents the results of tests of flow diameter and bulk density of fresh cement mixes, flexural tensile strength and compressive strength of hardened mortars, brittleness index, and the microstructure of seven-day-old, hardened mortars examined with a scanning electron microscope. Based on the conducted tests, it was demonstrated that replacing part of the natural aggregate with copper slag aggregate caused: a reduction in consistency and an increase in bulk density of fresh cement mixes, an increase in flexural tensile strength in later curing periods, and a reduction in compressive strength of hardened mortars, as well as extremely favorable values of the brittleness index compared to the reference mortar. Based on the obtained results, mineralization of copper slag with CO2 at 22°C was considered advantageous.